Pengembangan Lembar Kerja Peserta Didik Berbasis Metode Discovery Learning pada Materi Menulis Naskah Cerpen - Satriani Zega; Iman Pricalia Laoli; Iman Purnama Sari Laoli; Arozatulo Bawamenewi (Journal on Education, 2023)
The goal of this project is to create a discovery learning-based junior high school curriculum for Indonesian LKPD class VIII students that covers the subject matter "Writing Stories Manuscripts" and is appropriate for use in the classroom. This form of study is called development research and it has three stages: requirements assessment, design, and development and implementation. It uses a product-oriented learning paradigm. In order to examine the viability of LKPD, validation questionnaires for material experts, linguists, and design experts, as well as student response surveys, were used. By gathering quantitative and qualitative data from each validator and the students, data analysis was accomplished.